PERLINDUNGAN HUKUM BAGI KONSUMEN MUSLIM DALAM MENGKONSUMSI MAKANAN PADA RESTORAN HOTEL YANG BELUM MEMILIKI SERTIFIKAT HALAL DI KOTA PEKANBARU - Putri, Yunda Agusti; Ismi, Hayatul; Firmanda, Hengki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Pekanbaru, the population is predominantly Muslim, namely as many as 1,040,345 or 89.43%. This of course requires certainty regarding the food they eat, especially the food provided in hotel restaurants in Pekanbaru. The total Muslim population in Pekanbaru is 1,040,345 or 89.43%. In 2016, there were 30 hotel restaurants that did not have a halal certificate. In 2019 many hotel restaurants have halal certificates. Based on data obtained from BPJPH Pekanbaru, only 10 hotel restaurants have halal certification.This type of legal research is juridical sociological, which in this research, is carried out directly to the field to collect primary data, and uses descriptive methods. Meanwhile, if viewed from the nature of this research is descriptive.The results of this study are legal protection for Muslim consumers in consuming food at hotel restaurants that do not have a halal certificate in the city of Pekanbaru which is contained in Law Number 8 of 1999 concerning Consumer Protection, which only stipulates that business actors are prohibited from producing and / or trading goods and / or services that do not comply with the provisions of producing in a halal manner, as stated in the statement "halal" which is included in the label. However, Law Number 8 of 1999 concerning Consumer Protection does not explain the sanctions received by business actors who do not have a halal certificate. Likewise with Law Number 33 of 2014 concerning Guarantee of Halal Products. The law is to regulate the realization of halal certificates related to halal assurance of food products which are strengthened by government regulations, the Ministry of Religion and the Halal Product Guarantee Agency (BPJPH) with the aim of creating safety and comfort of food products, especially for Muslim consumers. However, the Law also does not explain the sanctions that are accepted for business actors who do not have a halal certificate. Implementation of the obligation to register a halal certificate for hotel restaurant owners in Pekanbaru city by means of BPJPH appealing to every producer or hotel restaurant owner to take care of ownership of a halal certificate. However, the problem is that the audit problem requires time and intense cooperation on the part of BPJPH to inspect and identify hotel restaurants that do not have a halal certificate.Keywords: Legal Protection, Muslim Consumers, Halal Certificate.